SIMULATION OF TUNNEL LINING AND SURROUNDING ROCK MASS RESPONSE TO CONSTRUCTION LOADS - MOHAMMED, JAAFAR A. (Journal of Duhok University, 2020)
The major design parameters related in tunnel engineering are loads, tunnel dimensions, geological and geotechnical properties of the ground surrounding the tunnel, which controls stresses and deformation of this underground structure. The effects of static loads during tunneling with shield Tunnel Boring Machine (TBM) on the rock mass and segmental concrete lining are considered. Applied static loads are (self-weight, drilling or excavation pressure, jack thrust, shield external pressure and segment external pressure). A comparison of the results of maximum total displacement and principal stresses of soft rock for different tunnel diameters including (D = 4, 6, 8, 10, 12 and 14 m) is performed. Tunnel lining of a circle tunnel were assumed to behave in a simple linear elastic way. Rock mass is assumed to be Isotropic, homogeneous and elastic rock in this modelling. The numerical analysis has been simulated and evaluated for each models separately. The thickness of tunnel lining for all models was assumed as 30 cm. The main concluding points of this study are to analyze the behaviour of tunnel lining and the surrounding rock under static loads during the construction processes using numerical modeling.